PREDICTING CHROMATOGRAPHIC BEHAVIOR OF SEVERAL CHIRAL β-BLOCKERS FROM MOLECULAR STRUCTURE BY QSPR ANALYSIS - TALMACIU , Mona-Maria; BODOKI, Ede; PLATTS, James; OPREAN, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The chiral HPLC separation parameters of a series of fourteen β-blockers previously performed on four polysaccharide-based chiral stationary phases (CSPs) was evaluated through computational techniques, using a set of 340 molecular descriptors (MD), calculated with the Molecular Operating Environment (MOE) software. Several semi-empirical mathematical models were built and refined by PLS, O2PLS multivariate data analysis and by PLS-Tree® clustering, correlating chromatographic data with the descriptors. The resulting models revealed the importance of certain analyze descriptors shaping chromatographic behaviour of the studied enantiomers. The chiral selector backbone as well as the presence of halogen atom(s) in the structure of the used stationary phase appears to exert an influence on the type of descriptors that significantly contribute either positively or negatively on the prediction power of the developed models. The influence of additive on the predictive power of models was also briefly analysed. This QSPR study generated models with a good predictive power. However, these results could be substantially improved in the future by including the descriptors for the chiral selectors and additives in the model and by performing docking studies.